Criminological Review of the Crime of Sexual Violence Against Children (Case Study in Banyumas Regency) - Imam Maulana Muhammad; Yusuf Saefudin (Proceedings Series on Social Sciences & Humanities, 2023)
This legal writing aims to examine factors in terms of Criminology of Sexual Violence Against Children handled by UPTD PPA Banyumas Regency. This research is included in the type of Normative research. This research uses secondary data. Secondary data is obtained through data on cases of sexual violence 2021 UPTD PPA banyumas district, books, scientific journals, and so on. The data collection technique used is literature study. The data analysis technique uses descriptive analysis. . Based on the results of the research, it can be obtained that the perpetrators of sexual violence against children must have committed their crimes due to the factors that cause crime, namely factors originating from within the perpetrator (internal factors) and factors from outside the perpetrator (external factors). From the data analysis, it was found that sexual violence against children was 86.84%, the gender of victims was dominated by women, 86.84%, the age of victims was dominated by 14-18 years old, 57.89%, the most common form of sexual violence was intercourse, 44.74%, victims of sexual violence were dominated by students, 76.32%, the most victims had a junior high school education, namely 44.74%, the relationship between the perpetrator and the victim was dominated by boyfriends and other people, namely 23.69%, the locus of sexual violence was most often found in the public domain, namely 57.89%, and the follow-up handling of sexual violence cases was mostly resolved by litigation, namely 84.21%.